Correlation Between Mother’s Role and Preparation of Teenage Girls in Facing Puberty Changeat Elementary School - Dina Putri Utami; vivi Nuryanti (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2018)
Introduction: During teenage will experience many changes both physically and psychologically. To deal with the changes that occur, teenage require readiness, both physically and psychologically. The role of the mother is one of the factors that affects readiness in facing the changes in puberty of the teenage. The purpose of this research was to know the correlation between the mother’s role and the readiness of teenage girl in facing the change of puberty of 8 until 12 years old at the elementary school Methods: This research type was quantitative with descriptive correlational design using cross sectional approach. The number of samples used were 37 respondents. Sampling technique used in this research was the purposive sampling technique with the data analysis using chi square test. The study was done in August 2017.Results: From the statistical test results obtained p-value of 0.001 (α <0.05) with a value of contingency of 0.485.Conclusions: There was a correlation between the mother’s role and the readiness of adolescent girls in facing the change of puberty at class II and Vat the elementary school with correlation of both variables in strong and unidirectional category.